APPARENT DIGESTIBILITY OF DIET DOMINANTLY COMPRISED OF PHYLLOSTACHYS VIVAX BAMBOO SHOOTS FOR CAPTIVE GIANT PANDAS - Z.G. Liu; C.D. Wang; J.L. Hu; F.M. Zhang; R. J. Linhardt; X.C. Lin (Journal of Animal and Plant Sciences, 2015)
This study, using the method of direct collection feces, investigated captive giant pandas daily intakes and apparent digestibility coefficients of diet dominantly comprised of Phyllostachysvivax bamboo shoots. The results showed that the captive giant pandas daily ingested ~2818 g (dry mass) of bamboo shoots (corresponding to ~42 kg of fresh bamboo shoots with shells). Based on this daily intake of bamboo shoots, we further analyzed the daily intakes of dietary components, including energy, crude protein, lipids, hemicelluloses, neutral detergent fiber (NDF), and acid detergent fiber (ADF). The results demonstrate that: i) the trials bamboo shoot diet provides giant pandas with sufficient and readily digestible, energy and crude protein; ii) the lipid (in low content) was efficiently utilized by giant pandas; and iii) the digestibility of fiber was very low in giant pandas.
Keywords: apparent digestibility; bamboo shoot; daily intake; giant panda; nutrient